THE STUDY HOW TO ASSEMBLING SMD DEVICE INTEGRATED - Wibowo, Kunto (Jurnal Ilmiah Informatika Komputer, 2008)
Nowadays, the size of electronic components is not macro anymore, but already in micro size, even nano. In designing electronic device using surface mount device (SMD), a number of special components which has better characteristics is oftentimes required because of the demand which can not be tolerated. Hermetic SMD (airproof SMD) is a preference to fulfill the demand for design of small size, light weight, perfect thermal performance, free of switching waves, and also higher circuit efficiency.Keyword(s): assembling, SMD, thermal performance, effcient.Subject Description : B.7.Integrated Circuit | B.7.1. Types and Design Styles | Advanced Technologies